Values Infusion: A Systematic Response to Catholic Identity - Krebbs, Mary Jane (Catholic Education: A Journal of Inquiry and Practice, 2000)
This article explains how the Archdiocese of New York responded to the need for making its values-based approach to education more conspicuous and formal. Through ECOS, a curricular change process, the Office of the Superintendent of Schools spearheaded a dialog and a program focusing on Catholic identity and values infusion as one source for the resurgence of that identity.